Earnings Management and Firm Value: The Activities of Independent Commissioners and Audit Committees as Proxies For Corporate Governance - Muhammad Ilham Pakawaru; Irham Pakawaru; Rika Febby Rhamdhani; Nurlailah (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study examines whether corporate governance, through the activities of independent commissioners and audit committees, mitigates earnings management and enhances firm value. Methods - This study employs a quantitative panel data approach using 90 firm-year observations from 18 State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during 2019-2023. Winsorization at the 5th and 95th percentiles was applied to Tobin’s Q, earnings management, and leverage, while other variables remained unchanged. Multicollinearity was assessed using the Variance Inflation Factor (VIF), and orthogonalization was applied to earnings management and interaction terms. Hypotheses were tested using Moderated Regression Analysis (MRA) with the Fixed Effects Model (FEM), selected based on the Chow and Hausman tests, using robust standard errors. Findings - Earnings management has a significant negative effect on firm value. Independent commissioners’ activities do not moderate this relationship, where audit committee activities significantly weaken its negative effect. Because audit committee activities are measured by cumulative attendance, the findings reflect monitoring intensity rather than monitoring effectiveness or governance quality. Greater audit committee participation is associated with preserving firm value. Research implications - The findings emphasize the importance of increasing audit committee participation in governance activities. Companies should strengthen oversight quality and corporate governance practices. Originality - This study contributes to the corporate governance literature by examining the moderating roles of Independent commissioners’ activities and audit committee activities. Unlike prior studies relying on structural governance measures, it uses cumulative meeting attendance to capture monitoring intensity, providing a behavioural perspective on corporate governance in Indonesian State-Owned Enterprises (SOEs).